THE GLOBAL CRISIS AND SMALL- AND MEDIUM-SIZED ENTERPRISES: THREAT OR CHALLENGE? - Simona Skorvagova; Janka Pasztorova (European Scientific Journal, ESJ, 2014)
SMEs play a significant role in all economies and are key drivers of employment, innovation and growth. SMEs have been especially hard hit by the global crisis. Due to their size and limited resources, in particular limited financial, managerial and information resources, they are more vulnerable to external shocks. With the economy facing the recession, companies are closing down and others are competing through spending cuts. Ongoing crisis has posed the significant challenge for small businesses and entrepreneurs. They need to take various measures against the economic shock to survive. This paper examines the possible changes in SMEs strategies that may be used to respond the unstable economic conditions in the world economy. The major attention is drawn especially to strategies based on the establishment of long-term relationships with stakeholders and on the strategies related to the cooperation between SMEs in order to innovate products/services or business processes.